The effect of using picture series to improve writing skills for third grade junior high school student's - Riantono, Agus; Edi Wibowo, Setiawan; Raharja, Setya; Zola, Nilma (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2024)
Writing is one of the language skills that is considered difficult because students are required to express ideas in written English correctly. This study aims to investigate the effect of using picture series in improving students’ writing skills. This study used experimental research in a junior high school. The results of this study indicate that the use of series of images has made a significant difference in improving students' writing skills. A series of images that are chosen appropriately can build students' interest and attention to the learning process. This will create an enthusiastic and lively learning atmosphere. Things that need to be considered are the selection of series of images that are easy and familiar to students to avoid irrelevant comments from students, series of images should not be funny images that will cause irrelevant comments and an uncontrolled classroom atmosphere. Giving students assignments individually can waste time in teaching writing using series of images. To avoid this, it is recommended to distribute copies of the picture series to students a week in advance, so that students can study the pictures early.